The LOFAR Two-meter Sky Survey: Deep Fields Data Release 1 III. Host-galaxy identifications and value added catalogues - Kondapally, R; Best, PN; Hardcastle, MJ; Nisbet, D; Bonato, M; Sabater, J; Duncan, KJ; McCheyne, I; Cochrane, RK; Bowler, RAA; Williams, WL; Shimwell, TW; et al. (EDP Sciences, 2021)
We present the source associations, cross-identifications, and multi-wavelength properties of the faint radio source population detected in the deep tier of the LOFAR Two Metre Sky Survey (LoTSS): the LoTSS Deep Fields. The first LoTSS Deep Fields data release consists of deep radio imaging at 150 MHz of the ELAIS-N1, Lockman Hole, and Boötes fields, down to RMS sensitives of around 20, 22, and 32 μJy beam-1, respectively. These fields are some of the best studied extra-galactic fields in the northern sky, with existing deep, wide-area panchromatic photometry from X-ray to infrared wavelengths, covering a total of ≈26 deg2. We first generated improved multi-wavelength catalogues in ELAIS-N1 and Lockman Hole; combined with the existing catalogue for Boötes, we present forced, matched aperture photometry for over 7.2 million sources across the three fields. We identified multi-wavelength counterparts to the radio detected sources, using a combination of the Likelihood Ratio method and visual classification, which greatly enhances the scientific potential of radio surveys and allows for the characterisation of the photometric redshifts and the physical properties of the host galaxies. The final radio-optical cross-matched catalogue consists of 81 951 radio-detected sources, with counterparts identified and multi-wavelength properties presented for 79 820 (>97%) sources. We also examine the properties of the host galaxies, and through stacking analysis find that the radio population with no identified counterpart is likely dominated by active galactic nuclei (AGN) at z ~ 3-4. This dataset contains one of the largest samples of radio-selected star-forming galaxies and AGN at these depths, making it ideal for studying the history of star-formation, and the evolution of galaxies and AGN across cosmic time.